A simple and inexpensive thermal optic nanosensor formed by triblock copolymer and polydiacetylene mixture - Ferreira, Gabriel Max Dias; Ferreira, Guilherme Max Dias; Hespanhol, Maria do Carmo; Rezende, Jaqueline de Paula; Pires, Ana Clarissa dos Santos; Ortega, Paulo Fernando Ribeiro; Silva, Luis Henrique Mendes da (Food Chemistry, 2017)
Polydiacetylene (PDA) vesicles have been applied as optical sensors in different areas, although there are difficulties in controlling their responses. In this study, we prepared nanoblends of PDA with triblock copolymers (TC) as a better sensor system for detecting temperature change. The influences of diacetylene (DA) monomer, and the TC chemical structure and concentration on the colorimetric response (CR) were examined. The TC/PDA nanoblend was remarkably more sensitive to temperature change, than classical vesicles. A higher L64 concentration of 12.0% (w/w) reduced the chromatic transition temperature (Ttr) to as low as 24 °C. When using different TCs, the Ttr values can be ordered as L35 < F68< L64 < F127<P123, indicating the importance of the hydrophobic environment for the colorimetric transition of nanoblends. The results here demonstrated that the balance of intermolecular interaction between TC-TC, TC-DA, and DA-DA enables the construction of strategic sensor for detecting temperature changes in different applications.
Keywords: Nanoblend; Colorimetric transition; Polymer interaction; Chromatic transition temperature; Thermosensor